Ameliorative influence of Baijin Pills on lithium-pilocarpine-induced epilepsy in mice: role of oxidative stress, neurotransmitters and multidrug resistant transporters - Jingbo Li; Xiaolan Cheng; Lian Xue; Hongquan Liu (Phytomedicine Plus, 2024)
Background: Oxidative stress, imbalance of neurotransmitters and multidrug resistant transporters play pivotal roles in the development and treatment of seizures. Classical formula Baijin Pills (BJP) has been used to treat brain damage caused by epilepsy for thousands of years. However, little information on the anti-seizure effects of BJP has been reported so far. Purpose: To investigate the effects of BJP on Lithium-pilocarpine- induced seizures and its role in the regulation of oxidative stress and neurotransmission. Study Design: The present study elucidates the anti-epileptic effects and mechanisms of action of BJP, using a mouse model of Lithium-pilocarpine- induced seizures. Methods: The antiepileptic effect of BJP was tested by fear conditioning test of mice model. Nissl staining showed neural loss and apoptosis in the hippocampus seizure mice and BJP treatment. Immunohistochemistry analysis of Bcl-2 and Bax inflected anti-apoptotic effects of BJP. The chemical colorimetric method was utilized to determine the effects of BJP on oxidative stress. The levels of excitatory and inhibitory neurotransmitters in cerebrospinal fluid (CSF) were detected by ELISA. Whole-cell votage-clamp recording was made to detect currents of receptor gated channels. Results: We found that BJP can significantly improve the cognitive disorders of epileptic mice, prolonged the latency of seizures and reduced the duration of epilepsy. BJP also effectively ameliorate neural injury in the hippocampus, up-regulated Bcl-2 protein level whereas decreased Bax expression. Moreover, the levels of SOD, GSH as well as γ-aminobutyric acid (GABA) were increased, while the levels of MDA, aminomethyl phosphonic acid (AMPA) and N-Methyl-D-aspartic acid (NMDA) were decreased in the hippocampus with BJP treatment. Patch clamp recording showed that BJP had no significant effect on the current induced by GABA, NMDA and AMPA in acutely isolated mice hippocampal neurons. Furthermore, BJP inhibited the expression of P-gp, MRP1 and MDR1 protein. Conclusions: Our study provides the first experimental basis that BJP can exert anti-seizure effects by attenuating oxidative stress, regulating neurotransmission and inhibit drug-resistant associated proteins. BJP may be developed as a drug candidate to treat epilepsy in clinical practice.